Irrigation and nitrogen management in protein content and quality of common bean seeds - Matheus Gustavo da Silva; Aliston Flávio de Souza; Gustavo Henrique Ferreira da Silva; Adriano da Silva Lopes; Paulo Eduardo Teodoro (Bioscience Journal, 2017)
The aim of this study was to investigate the influence of different irrigation managements and nitrogen topdressing rates on the protein content and physiological quality of common bean seeds. Trial was conducted at Universidade Estadual de Mato Grosso do Sul, Unidade Universitária de Aquidauana from June to September, 2010. Experimental design was a randomized block in a split plot, using three blocks and two replications within each block. Plots corresponded to three irrigation managements: Hargreaves-Samani, Penman-Montheith and Class A pan. Subplots were represented by four N topdressing rates (zero, 50, 100 and 150 kg ha-1). The following variables were evaluated: 100-seed mass, nitrogen and crude protein content in seeds, germination at field, germination at laboratory, accelerated aging and germination speed index. There was a significant interaction between the different irrigation management and nitrogen topdressing rates for nitrogen and crude protein content in seeds, germination at laboratory and emergence speed index. Levels between 70 and 120 kg ha-1 N in conjunction with irrigation management by Hargreaves-Samani method provide better physiological quality of common bean seeds.